The "In-Between": caribbean and the white creole in Jean Rys's wide sargasso sea and Phyllis Allfrey's the orchid house - Habib, Sarah (BRAC University, 2013)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2014.